Bloody engagements : John R. Kelso's Civil War - Kelso, John R. (John Russell), 1831-1891 (Yale University Press, 2017)
While tales of Confederate guerilla-outlaws abound, there are few scholarly accounts of the Union men who battled them. This edition of John R. Kelso's Civil War memoir presents a firsthand account of an ordinary man's extraordinary battlefield experiences along with his evolving interpretation of what the bloody struggle meant.